Effect of dietary flaxseed meal supplemented with dried tomato and grape pomace on performance traits and antioxidant status of laying hens. Issue 7 (12th December 2022) - Tufarelli, Vincenzo; Baghban-Kanani, Payam; Azimi-Youvalari, Saba; Hosseintabar-Ghasemabad, Babak; Slozhenkina, Marina; Gorlov, Ivan; Viktoronova, Frolova Maria; Seidavi, Alireza; Laudadio, Vito
Abstract: This study was carried out to determine the effect of dietary flaxseed meal (FSM) supplemented with dried tomato pomace (DTP) and dried grape pomace (DGP) on performance, egg quality, biochemical parameters traits and antioxidant status of laying hens. Birds (1825 ± 87 g of body weight) were divided into 12 dietary groups with six replicates per group (eight birds per replicate), under a completely randomized design with factorial arrangement 2 × 3 × 2 consisted of two levels of DTP (0 and 15%), three FSM levels (0, 4 and 8%) and two levels of DGP (0 and 5%). As a result of this study, there were no significant differences in egg production and weight as well in feed conversion ratio (FCR) among treatments ( p > 0.05). Feeding of DGP reduced significantly feed intake and egg mass when compared to control group ( p < 0.05). There was no effect ( p > 0.05) of dietary treatment on shell thickness and strength, shape index, Haugh unit and egg specific gravity. Hens consuming 15% DTP and 5% DGP revealed a significantly higher yolk color compared to the other dietary treatments ( p < 0.05). Moreover, there was no difference among dietary treatments in terms of serum low-density lipoprotein cholesterol (LDL) and high-density lipoprotein cholesterol (HDL) cholesterol, atherogenic index, triglycerides, total cholesterol levels ( p > 0.05). Serum antioxidant parameters as glutathione peroxidase (GSH-Px) activity, malondialdehyde (MDA), total superoxide dismutase (TSOD) and total antioxidant capacity (T-AOC) were not influenced by treatments ( p > 0.05). Based on findings, FSM and DTP supplements did not significantly impact most of hens' performance indicators and egg quality parameters, whereas significant improvements were observed by feeding of 15% DTP and 5% DGP on egg traits, in particular on egg-yolk color that plays a key-role in consumer's choice. However, the supplementation of FSM and DTP or DGP even in laying hen diet is still controversial and further research is needed.